Strategies for Using Muramyl Peptides - Modulators of Innate Immunity of Bacterial Origin - in Medicine - Guryanova, Svetlana V.; Khaitov, Rahim M. (Frontiers in Immunology, 2021)
The spread of infectious diseases is rampant. The emergence of new infections, the irrational use of antibiotics in medicine and the widespread use in agriculture contribute to the emergence of microorganisms that are resistant to antimicrobial drugs. By 2050, mortality from antibiotic-resistant strains of bacteria is projected to increase to 10 million people per year, which will exceed mortality from cancer. Mutations in bacteria and viruses are occurring faster than new drugs and vaccines are being introduced to the market. In search of effective protection against infections, new strategies and approaches are being developed, one of which is the use of innate immunity activators in combination with etiotropic chemotherapy drugs. Muramyl peptides, which are part of peptidoglycan in the cell walls of all known bacteria, and are regularly formed in the body during the breakdown of microflora, are natural regulators of immunity. Their interaction with intracellular receptors launches a sequence of processes that ultimately lead to increased expression of genes of MHC molecules, pro-inflammatory enzymes and mediators, cytokines, their soluble and membrane-associated receptors, as a result, all subpopulations of immunocompetent cells are activated: macrophages and dendritic cells, neutrophils, T - and B-lymphocytes, natural killer cells for an adequate response to foreign or transformed antigens, manifested both in the regulation of the inflammatory response and in providing immunological tolerance. Muramyl peptides take part in the process of hematopoiesis, stimulating the production of colony-stimulating factors, and it was the basis for their use in the treatment of oncological diseases. The review discusses clinical trials of drugs based on muramyl peptides, as well as the clinical efficacy of drugs mifamurtide, lycopid, liasten and polimuramil. Such a multifactorial effect of muramyl peptides and a well-known mechanism of activity makes them promising drugs in the treatment and preventing of infectious, allergic and oncological diseases, including in the composition of vaccines.